PENGARUH DISIPLIN DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA PT GARUDA INDONESIA - Dadang Surya Kencana; Elis Chalisyah (POLITEKNIK LP3I JAKARTA, 2024)
Human Resources (HR) is an important aspect in an organization or company, having quality human resources will make a company grow further in facing various existing business competitions, and vice versa. One of the factors that is very influential in HR is a discipline factor. Work discipline can be seen as having great benefits, both for the interests of the organization and for employees. For organizations, the existence of work discipline will ensure the maintenance of order and smooth implementation of tasks, so that optimal results are obtained. Apart from work discipline, an employee's work stress will certainly influence a company's performance. If stress is high it will further reduce performance and vice versa. This research aims to see whether There is The influence of work discipline and work stress on employee performance at PT Garuda Indonesia, with using the Multiple Linear Regression Analysis method with the help of the SPSS program. Based on the analysis and discussion, it is concluded that work discipline has a positive influence on employee performance, while work stress has a negative influence on employee performance. Therefore, it can be interpreted that work discipline must be maintained and improved, while work stress must be reduced. Key words: Employee Performance, Work Discipline, and Work Stress